Secondary Education for Ethnic Children: Opportunities and Challenges (Bangladesh Journal of Educational Research, 2026)
Secondary education is a core component of the education system in Bangladesh, serving as the bridge between primary and tertiary levels. The primary objective of this paper is to examine the current state of secondary educational opportunities available to ethnic children, as well as the challenges they typically encounter. Using a mixed‑methods approach, data were collected through an interview schedule, a school information sheet, and focus group discussions with teachers and students. A total of 30 secondary schools were selected as the primary sample units. The findings indicate that most schools have an insufficient number of teachers and classrooms, both in rural and urban areas. Toilets are available for teachers, girls, and boys; however, they are often unhygienic. Moreover, ethnic students in secondary schools face a range of difficulties, including economic hardship, communication barriers, security concerns, political and racial issues, and family and societal pressures.